[Re]creating the lived experiences of women in a struggle for agrarian reform in Hacienda Luisita - Rigor, Lodigario A. Jr. & Daya, Romel A. (The Philippine Journal of Development Communication, 2013)
The life of women in agrarian reform community (ARC) is one of the development issues less explored by scholars of development communication (DevCom) in the Philippines. This research was a scholarly attempt to understand agrarian reform struggle as a lived experience of women in Hacienda Luisita, an ARC widely reported in the Philippine media. It tried to situate DevCom in a politically charged environment of development in ARCs. Its epistemological and methodological groundwork was classical phenomenology, which underscores disciplined experience of the other's world through dialogue and reflection without bringing one's own categories in the process. Five women from one agrarian reform organization in the hacienda were purposefully chosen as participants of the study. This paper discusses their understanding of a struggle that was shaped by various constitutive forces they experienced in their fight for land. Sacrifice was considered as the essence of the struggle.